Alteration of the Route to Menaquinone towards Isochorismate‐Derived Metabolites. (24th May 2019) - Fries, Alexander; Mazzaferro, Laura S.; Grüning, Björn; Bisel, Philippe; Stibal, Karin; Buchholz, Patrick C. F.; Pleiss, Jürgen; Sprenger, Georg A.; Müller, Michael
Abstract: Chorismate and isochorismate constitute branch‐point intermediates in the biosynthesis of many aromatic metabolites in microorganisms and plants. To obtain unnatural compounds, we modified the route to menaquinone in Escherichia coli . We propose a model for the binding of isochorismate to the active site of MenD ((1 R, 2 S, 5 S, 6 S )‐2‐succinyl‐5‐enolpyruvyl‐6‐hydroxycyclohex‐3‐ene‐1‐carboxylate (SEPHCHC) synthase) that explains the outcome of the native reaction with α‐ketoglutarate. We have rationally designed variants of MenD for the conversion of several isochorismate analogues. The double‐variant Asn117Arg–Leu478Thr preferentially converts (5 S, 6 S )‐5, 6‐dihydroxycyclohexa‐1, 3‐diene‐1‐carboxylate (2, 3‐ trans ‐CHD), the hydrolysis product of isochorismate, with a >70‐fold higher ratio than that for the wild type. The single‐variant Arg107Ile uses (5 S, 6 S )‐6‐amino‐5‐hydroxycyclohexa‐1, 3‐diene‐1‐carboxylate (2, 3‐ trans ‐CHA) as substrate with >6‐fold conversion compared to wild‐type MenD. The novel compounds have been made accessible in vivo (up to 5.3 g L −1 ). Unexpectedly, as the identified residues such as Arg107 are highly conserved (>94 %), some of the designed variations can be found in wild‐type SEPHCHC synthases from other bacteria (Arg107Lys, 0.3 %). This raises the question for the possible natural occurrence of as yet unexplored branches of the shikimate pathway. Abstract : Unnatural chorismate‐derived metabolites : The route to menaquinone has been modified and the substrate range of the enzyme MenD tailored for the synthesis of nonphysiological compounds. The results demonstrate that a few mutations are sufficient to modify substrate recognition by MenD, hence raising the question of the occurrence of these or similar, but so far unknown, transformations in nature.